DOI: 10.1007/978-1-4020-8837-7_16
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotactic Bacteria and Their Potential for Terraformation

Abstract: His scientific interests are in the areas of: bacteria-based biosensors, hydrogen metabolism in phototrophic bacteria, biology of magnetotactic bacteria and their relevance for bionanotechnology and terraformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…As perspectives in our research we focus on the following: the potential of MTB for terraformation (2), elaboration of a magnetic model of magnetotactic bacteria (1; 8; 12; 21) heavy metal biosorbtion and gold nanoparticles synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…As perspectives in our research we focus on the following: the potential of MTB for terraformation (2), elaboration of a magnetic model of magnetotactic bacteria (1; 8; 12; 21) heavy metal biosorbtion and gold nanoparticles synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that about 25% population of ALH84001 magnetic crystals are identical to biologically produced crystals Thomas-Keprta et al (2001). Ardelean et al (2008) also focused on possible contributions of MTB to the terraformation of Mars or other planets. Although, there are credible arguments and supports for both the non-biogenic and biogenic hypothesis for the origin of the magnetite particles in ALH84001 meteorite, yet if it's biological origin is proved, such magnetofossils would constitute evidence of the oldest life forms known.…”
Section: As Bio Indicatormentioning
confidence: 99%
“…As mentioned earlier, MTB use the magnetosomes for geomagnetic navigation in their aquatic habitat, i.e., magnetotaxis. It has been proposed that, in natural environments, magnetotaxis may enable the cells to locate and maintain an optimal position in the water column or in sediments, and that this aligns with their main metabolic needs [31]. The magnetic assisted taxis could help MTB in their navigation toward optimum growth conditions [7]; hence, growing MTB under optimum conditions may in fact inhibit magnetosome production.…”
Section: Metallic Nanoparticle Synthesis By M Magnetotacticum Using E...mentioning
confidence: 99%